Surveys on forecasting used in commercial enterprises : laporan teknik - 494380 Zuhaimy Ismail; Maizah Hura Ahmad; Universiti Teknologi Malaysia. Fakulti Sains. Jabatan Matematik (Skudai : Universiti Teknologi Malaysia, 2000)
36